The Importance Of A Healthy Lifestyle In Maintaining The Health Of The Population - Rana Shomuratovna Baratova (Genius Journals, 2023)
The life and health of every person is the greatest social wealth of society. In this family, the school puts the issue of forming a healthy lifestyle in front of the places dealing with human education and development. Everyone's health is naturally determined by a healthy lifestyle.
Keywords: intellectual; lifestyle; hypodynamia; cocktail productivity